2013
DOI: 10.1177/2150131913498513
|View full text |Cite
|
Sign up to set email alerts
|

No-Show to Primary Care Appointments

Abstract: No-show rates interfere with quality primary care. Interventions designed to target reasons for no-show are needed to help reduce the no-show rate, improve access and decrease health disparities in underserved patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
117
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(147 citation statements)
references
References 18 publications
(22 reference statements)
9
117
3
3
Order By: Relevance
“…[1][2][3][4][5] The impact is particularly important within safety net organizations, which primarily care for underserved patients and which often operate with limited resources. 3 This pragmatic investigation of the impact of short message service (SMS) text message appointment reminders was conducted as part of Denver Health's (DH) 21 st Century Care program, funded under a Health Care Innovation Award grant from the Center for Medicaid and Medicare Innovation to explore the impact of novel models of care on the triple aim (1C1CMS331064-01-00). Previous SMS reminder studies have shown improved attendance rates.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The impact is particularly important within safety net organizations, which primarily care for underserved patients and which often operate with limited resources. 3 This pragmatic investigation of the impact of short message service (SMS) text message appointment reminders was conducted as part of Denver Health's (DH) 21 st Century Care program, funded under a Health Care Innovation Award grant from the Center for Medicaid and Medicare Innovation to explore the impact of novel models of care on the triple aim (1C1CMS331064-01-00). Previous SMS reminder studies have shown improved attendance rates.…”
Section: Introductionmentioning
confidence: 99%
“…Only 40% of patients completed all three ReDCHiP CM sessions, despite being less timeintensive than most programs in randomized trials. [15][16][17] With a 20% to 40% patient no-show rate to PCP appointments, 22 our completion rates for three appointments in three months may be expected. Efficacy trials in which patients received CM at least monthly have shown more BP improvement than those in which patients received CM less frequently.…”
Section: Care Management To Control Hypertension -Hussain Et Almentioning
confidence: 99%
“…Care managers were unable to contact half of eligible patients, similar to other health systems using automated outreach. 22 CM for complex disease management that is integrated with primary care has been shown to be most effective; 8 however, program completion and/or reach may be improved if CM could be integrated within the daily routine of patients (at faith organizations, employment sites). 24 Additional intervention components for highrisk and frail patients (home visits, community health workers) may improve reach and completion.…”
Section: Care Management To Control Hypertension -Hussain Et Almentioning
confidence: 99%
“…They also add significant burden on healthcare systems worldwide and lead to sub-optimal utilization of resources [4][5][6]. Reasons frequently cited by patients missing their appointments are "forgetting the appointment" or "misunderstanding the date or time of the appointment" or "lack of motivation to go to the appointment" [7][8][9][10]. Phone calls, postal, and text reminders have been extensively studied as memory aids to reduce missed appointments [11][12][13].…”
Section: Prior Workmentioning
confidence: 99%